Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan Pada Sektor Infrastruktur, Utilitas dan Transportasi - Caroline Janet Sukamto; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
There is still an inconsistency between theory and empirical results regarding the influence of family ownership structures on firm performance. On the theory, family ownership structure has advantages that can provide benefits to the improvement of firm performance. On the other hand, there are many empirical results regarding the positive and negative effects of family ownership structures on firm performance. This study aimed to examine and to prove the influence of family ownership structure on firm performance. The family ownership structure was measured by the presence or absence of family members sitting in the managerial position of the company or the ownership of stock by the family at least ten percent. Company performance was measured by using ROA. There were two control variables used: GCG score and market share. This research was conducted on public company of infrastructure, utility and transportation sectors which listing in IDX in 2010-2015 with a sample of 125 observations. The result showed a significant negative relationship between family ownership structure with ROA. The result of this study also showed that GCG score had a significant positive affect on ROA, while market share had no affect on ROA.